'Molecular habituation' as a potential mechanism of gradual homeostatic loss with age. (January 2018) - Martinez Guimera, Alvaro; Welsh, Ciaran M.; Proctor, Carole J.; McArdle, Anne; Shanley, Daryl P.
Highlights: Constitutive signals indicate homeostatic dysregulation but their effect on signal transduction remains largely unexplored. A theoretical approach is undertaken to examine how oxidative stress may affect redox signal transduction. Constitutive signals can result in a 'molecular habituation' effect that interferes with information transmission. The robustness of such a theoretical observation to the underlying methodology hints at the generality of this principle. Abstract: The ability of reactive oxygen species (ROS) to cause molecular damage has meant that chronic oxidative stress has been mostly studied from the point of view of being a source of toxicity to the cell. However, the known duality of ROS molecules as both damaging agents and cellular redox signals implies another perspective in the study of sustained oxidative stress. This is a perspective of studying oxidative stress as a constitutive signal within the cell. In this work, we adopt a theoretical perspective as an exploratory and explanatory approach to examine how chronic oxidative stress can interfere with signal processing by redox signalling pathways in the cell. We report that constitutive signals can give rise to a 'molecular habituation' effect that can prime for a gradual loss of biological function. This is because a constitutive signal in the environment has the potential to reduce the responsiveness of a signalling pathway through the prolonged activation of negative regulators. Additionally, we demonstrate how this phenomenon is likely to occur in different signalling pathways exposed to persistent signals and furthermore at different levels of biological organisation.